Habitos oviposicionales de Spodoptera frugiperda (J.E. Smith)(Lepidoptera:Noctuidae) en plantas de arroz - Ayala Sifontes, J.L.=700 1 Ramirez Obregon, J.; Rodriguez Cuellar, S.; Armas Garcia, J.L.
(En, Es)
ilus., 3 ref.
Keywords: ARROZ; SPODOPTERA FRUGIPERDA; OVIPOSICION; CUBA